Social mobilization for the safeguarding of cultural heritage. : An analysis of cases in an intermediate city in Buenos Aires Province, Argentina - Cantar, Nahir Meline (2023)
Studies about the involvement of communities in patrimonialization processes tend to focus on isolated cases without considering the impact of the problem on the whole society. Therefore, this paper describes two social mobilizations cases in architectural heritage defence (Olavarría, Argentina) to expand the analysis concerning the different actors' perceptions of the issue. Methodologically, we analyze different sources, such as social networks, interviews and a questionnaire to 390 inhabitants. The results contextualize perceptions that do not correspond to a single form of action but deploy many meanings that allow us to think of cultural heritage as a public good whose sustainability is not equally valued by the community.